PENERAPAN ASAS KESEIMBANGAN PADA NOMINAL HARGA PENJUALAN MYSTERY BOX DI MARKETPLACE SHOPEE BERDASARKAN HUKUM PERLINDUNGAN KONSUMEN - Anggi Patresia Damanik (2023)
Mystery box buying and selling is one of the interesting types of buying and selling transactions that are in great demand by the public today, but behind its uniqueness a number of problems arise. One of them is that shops often set a nominal price that is not balanced or in accordance with the contents of the mystery box. Given the concept of buying and selling mystery boxes, namely buyers do not know exactly what goods they will get, so that in this case consumers are in a vulnerable position. This study aims to analyze the application of the principle of balance to the nominal selling price of mystery boxes in the marketplace shopee and to find out what are the indicators of the application of the principle of balance. This research is a type of normative research presented in the form of qualitative analysis, which originates from literature studies and case studies on primary, secondary and tertiary legal materials. The results of this study indicate that the principle of balance has not yet been applied to the nominal price of mystery boxes in the marketplace, because there are still cases of shops sending goods with market price ranges that are far below the price of the mystery box. The author found that there were 3 things that became indicators of the application of the balance principle in determining the selling price of mystery boxes, which could be measured based on the seller's good faith, the quality and quality of the goods and feedback from consumers. The quality and quality of these goods can be seen through sellers who send damaged goods, expired goods, used goods and empty goods. For this reason, it is necessary to apply the principle of balance in terms of determining the nominal selling price of mystery boxes in order to reduce the level of losses for consumers. Keywords: Mystery Box, Balance Principle, Price